A Study of STEM Assessments in Engineering, Science, and Mathematics for Elementary and Middle School Students. (February 2015) - Harwell, Michael; Moreno, Mario; Phillips, Alison; Guzey, S. Selcen; Moore, Tamara J.; Roehrig, Gillian H.
<x xml:space="preserve">Abstract</x> The purpose of this study was to develop, scale, and validate assessments in engineering, science, and mathematics with grade appropriate items that were sensitive to the curriculum developed by teachers. The use of item response theory to assess item functioning was a focus of the study. The work is part of a larger project focused on increasing student learning in science, technology, engineering, and mathematics (STEM)‐related areas in grades 4–8 through an engineering design‐based, integrated approach to STEM instruction and assessment. The fact that the assessments are available to school districts at no cost, and represent psychometrically sound instruments that are sensitive to STEM‐oriented curriculum, offers schools an important tool for gauging students' understanding of engineering, science, and mathematics concepts.